The Wicked Prince - Andersen, Hans Christian (Saga Egmont, 2020)
Once upon a time there was a prince without pity: he wanted to be the strongest and sent armies of soldiers to destroy villages and stop other kings, he even got it into his head to prove that he was worth more than God… Little did he know where this arrogance would lead him! Hans Christian Andersen (1805-1875) was a Danish author, poet and artist. Celebrated for children’s literature, his most cherished fairy tales include "The Emperor's New Clothes", "The Little Mermaid", "The Nightingale", "The Steadfast Tin Soldier", "The Snow Queen", "The Ugly Duckling" and "The Little Match Girl". His books have been translated into every living language, and today there is no child or adult that has not met Andersen's whimsical characters. His fairy tales have been adapted to stage and screen countless times, most notably by Disney with the animated films "The Little Mermaid" in 1989 and "Frozen", which is loosely based on "The Snow Queen", in 2013. Thanks to Andersen's contribution to children's literature, his birth date, April 2, is celebrated as International Children's Book Day.